SOLIVA ANTHEMIFOLIA (JUSS.) R.BR. (ASTERACEAE) : A NEW GENERIC RECORD TO THE FLORA OF CHHATTISGARH - Shukla, Sandeep (Current Botany, 2017)
The present paper highlights the occurrence of Soliva anthemifolia (Juss.) R.Br. as a new generic record to the flora of Chhattisgarh collected from Pendra village of Bilaspur district. Notes on its morphological characters, habit and habitat are provided in the article.